Development of Critical Thinking Model in History Learning - Purmintasari, Yulita Dewi; Suwarni, Suwarni; Eviliyanto, Eviliyanto; Billy, Jonatan (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The aim of this research is to develop a critical thinking model and determine students' critical thinking abilities because critical thinking skills are very important for students to master to be able to explain logically in reconstructing historical events. The research method used in this research is development research using the ADDIE procedure (Analyze, Design, Develop, Implement and Evaluate). Data collection techniques use observation, direct communication, and documents, while the tools use observation guides, interview guides, and expert validation sheets. The data analysis technique using quantitative descriptive is used as a technique for reviewing research findings, with stages of data selection, data tabulation, calculating alternative answers. The results of the category validation research were very good with an average score of 4.38. The results of the feasibility test are very good with an average score of 4.49, product implementation shows that the results of the effectiveness test show that critical thinking skills as seen from the learning results using the model developed have higher results.